2015
DOI: 10.1080/1573062x.2014.991328
|View full text |Cite
|
Sign up to set email alerts
|

Climate, land use and hydrologic sensitivities of stormwater quantity and quality in a complex coastal-urban watershed

Abstract: We determined reference hydro-climatic and land use/cover sensitivities of stormwater runoff and quality in the Miami River Basin of Florida by developing a dynamic rainfall-runoff model with the EPA Storm Water Management Model. Potential storm runoff in the complex coastal-urban basin exhibited high and notably different seasonal sensitivities to rainfall; with stronger responses in the drier early winter and wetter late summer months. Basin runoff and pollutant loads showed moderate sensitivities to the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The Storm Water Management Model (SWMM) is among the most widely used software for simulating rainfall‐runoff in urban areas (Lee, Hewa, Pezzaniti, & Argue, 2008; Sun, Hall, Hong, & Zhang, 2014; Abdul‐Aziz & Al‐Amin, 2015; Yu, Huang, & Wu, 2014;). SWMM is a physical model, whose runoff module deals with precipitation, runoff, and pollution load of each sub‐basin.…”
Section: Introductionmentioning
confidence: 99%
“…The Storm Water Management Model (SWMM) is among the most widely used software for simulating rainfall‐runoff in urban areas (Lee, Hewa, Pezzaniti, & Argue, 2008; Sun, Hall, Hong, & Zhang, 2014; Abdul‐Aziz & Al‐Amin, 2015; Yu, Huang, & Wu, 2014;). SWMM is a physical model, whose runoff module deals with precipitation, runoff, and pollution load of each sub‐basin.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is still lack of consistency in research findings when it comes to future scenarios based on different levels of urban development. Abdul‐Aziz and Al‐Amin investigated the sensitivities of stormwater quantity and quality in a coastal urban watershed (the Miami River Basin of Florida) based on certain climate change scenarios and changing land use, and found that runoff quantity exhibited high sensitivity, which also varied seasonally . Willuweit et al stimulated the effects of climate change and economic and urban planning scenarios on urban runoff patterns in Dublin, Ireland, and found that climate change is likely to reduce runoff, while urbanization is likely to increase it, and that decentralized practices have a critical role in sustainable urban stormwater management .…”
Section: Introductionmentioning
confidence: 99%
“…SWMM is a catchment scale model and provides an integrated environment for editing input data for a given study area and results can be viewed in a number of formats [11]. Several studies have utilized SWMM, including Lee [3], Sun, Hall, Hong and Zhang [11], Wella-Hewage [8], Abdul-Aziz and Al-Amin [12] and Yu et al [13], for low flow studies, catchment discretization, Water Sensitive Urban Design (WSUD) methodology development, runoff and pollutant modelling and drainage system analysis, respectively. Though the model has numerous advantages and has a wide range of applications, it does not have any spatial interface.…”
Section: Introductionmentioning
confidence: 99%